State Ocean Jurisdiction - Vrancken, Patrick (Routledge Research on the Law of the Sea, 2023)
Proposing a systematic analytical framework which assists in understanding and applying the international law regime governing State ocean jurisdiction with a view to improved ocean governance for sustainable development, this book distinguishes between, and focuses on, the form, the ground, the scope and the purpose of State ocean jurisdiction. Defining jurisdiction as the international-law authority of a State to be involved in a factual matter on the basis of a valid legal ground to perform authoritative acts impacting on that matter, it disaggregates the concept the complexity of which often leads to States failing to make full use of their existing ocean jurisdictions. In the process, it identifies when and to what extent there are gaps and overlaps of jurisdictions. Bringing clarity on an inevitably complex and often misunderstood framework that is aimed at striking a universally accepted balance of competing interests, the book lays the foundation for future research, contextualising the position of State ocean jurisdiction not only in terms of ocean governance, but in the whole of public international law. With an original systematic focus on State ocean jurisdiction, the book will be of interest to academics, students and practitioners working in the areas of international law of the sea, ocean governance, human rights and environmental law.